Extrapair paternity in two populations of the socially monogamous Thorn-tailed Rayadito Aphrastura spinicauda (Passeriformes: Furnariidae) - Botero Delgadillo, Esteban (2020)
Studies on extrapair paternity (EPP) are key to understanding the ecological and evolutionary drivers of variation in avian mating strategies, but information is currently lacking for most tropical and subtropical taxa. We describe the occurrence of EPP in two populations of a South American socially monogamous bird, the Thorn-tailed Rayadito, based on data from 266 broods and 895 offspring that were sampled during six breeding seasons in north-central and southern Chile. In the northern population, 21% of the broods contained at least one extrapair young and 14% of all offspring were sired by an extrapair male, while in the southern population, we detected extrapair offspring (EPO) in 14% of the broods, and 6% of all offspring were EPO. Variation in the frequency of EPP could stem from population differences in the duration of the breeding season or the density of breeding individuals. Other factors such as differences in breeding synchrony and variation in food availability need to be evaluated. More reports on EPP rates are necessary to determine the patterns of taxonomic and geographic variation in mating strategies in Neotropical birds, and to better understand the differences in ecological dynamics between northern and southern hemisphere populations.